Teaching Online: Lessons from the COVID-19 Pandemic and the End of the Teacher-Priest - Marsili, M. (e-Instructor Insights: Applying the lessons of Pandemic Learning, 2023)
Teaching at higher education institutions relies traditionally on ex-cathedra methods. The COVID-19 pandemic blasted online education years into the future and exposed its many challenges. Technology has provided smart and innovative solutions for distance education, which have opened up new teaching methods and techniques and boosted the internationalization of higher education. While critics of these innovations denounce alleged flaws, the benefits are likely to be greater than the costs, a turning point in teaching that is difficult to back down from.